Prevalence and correlates of probable post-traumatic stress disorder and common mental disorders in a population with a high prevalence of HIV in Zimbabwe. Issue 1 (1st January 2018) - Verhey, R.; Gibson, L.; Brakarsh, J.; Chibanda, D.; Seedat, S.
ABSTRACT: Background : We investigated the prevalence of and factors associated with post-traumatic stress disorder (PTSD) and common mental disorders (CMDs), which include depression and anxiety disorders, in a setting with a prevalence of high human immunodeficiency virus (HIV) within a primary care clinic, using the PTSD Checklist for DSM-5 and the 14-item Shona Symptom Questionnaire, both locally validated screening tools. Methods : A cross-sectional survey was carried out with adult patients ( n = 204) from the largest primary care clinic facility in Harare, Zimbabwe, in June 2016. Results : A total of 83 patients (40.7%) met the criteria for probable PTSD, of whom 57 (69.5%) had comorbid CMDs. Among people living with HIV, 42 (55.3%) had PTSD. Probable PTSD was associated with having experienced a negative life event in the past 6 months [adjusted odds ratio (OR) 3.73, 95% confidence interval (CI) 1.49–9.34] or screening positive for one or more CMD (adjusted OR 6.48, 95% CI 3.35–2.54). Conclusion : People living with HIV showed a high prevalence of PTSD and CMD comorbidity. PTSD screening should be considered when the CMD screen is positive and there is a history of negative life events.